(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: The Family Adoption Program (FAP), newly mandated by National Medical Commission for all MBBS students aims to provide an experiential learning opportunity for them towards community-based health care. This study was conducted to assess the profile of the MBBS students, their perception and of the families adopted by them on FAP. Materials and Methods: A cross-sectional study was conducted in 2023 including 100 medical students of Rajiv Gandhi Medical College. After sensitization to the FAP proforma, each student was allotted five families for adoption from the Lokmanya Nagar located in the outskirts of Thane city. Students recorded details of families in the proforma. Feedback and perception on FAP from the families as well as from students were collected. The data was analyzed using Microsoft Excel. ꭓ2 test was applied. Results: Out of 100 students, 48% students were males and 52% were females. 96% students were in the age group of 17-20 years and 4% were of aged >20 years. 98% of the medical students were told by the adopted families that FAP is a good initiative. All the students mentioned in the feedback, FAP will help to develop leadership skill among them, will help to enhance the health of the adopted families and will surely improve the communication skill of the Indian Medical Graduates which will be useful for their professional growth. Conclusions: All students were delighted and gratified with this program and the same was mentioned by them in the feedback. FAP will create a significant difference in medical education and will definitely help to promote health of the adopted families.